Development of mobile robot for measuring distance using optical quadrature encoder - Madiha Zahari; NurliyanaAbd Mutalib; Nurnadia Natasya Affendi; N. Hashim; D. A. Hadi; Siti Halma Johari; N. Ab Wahab; Suziana Ahmad (Institute of Advanced Engineering and Science, 2020)
This paper describes the design and development of a measuring tool using a mobile robot. At present, contractors are measuring distances using measuring tape which has few limitations. This includes using of another manpower or a marking flag. The Robot Measuring System is designed to measure distances at multiple conditions such as smooth and rough surface. An optical quadrature encoder is used as a sensor to measure the distances while a program is installed in Arduino Uno for reading and data collection. Graphical User Interface (GUI) was created using Android software so that the movement of the robot can be controlled using a smartphone within a Bluetooth range. An experiment was conducted to test the reliability in terms of accuracy and precision. The best accuracy and precision were obtained when the robot speed is at 90 cm/s on the plain tiles, 80 cm/s on the tar road and 90 cm/s on the grass surface. The robot speed needs to be adjusted accordingly based on the surfaces in order to get an accurate result. This paper proved that the robot measuring system was successfully designed, implemented and analyzed.